Correlación de la formalización administrativa con los ingresos de las micro y pequeñas empresas comerciales especializadas en tecnología en Quito - Córdova Ballesteros, Luis Felipe; Gutiérrez Burbano, Jairo Alexander; Ojeda Zambrano, Carla de los Angeles (SATHIRI, 2019)
The administrative formalization of an organization is evident from two clearly differentiated areas: legalization as a legal entity in society and also how the internal processes are declared and documented for the knowledge and application of its personnel.The objective of this cross-sectional descriptive study is to measure and describe the second type of formalization in micro and small-scale companies specialized in the retail trade of technology and communication equipment (ISIC 474) in the urban parishes of the city of Quito and to determine if it is related to the level of revenue (gross sales) in 2016. After applying the methodology to 61 managers of micro and small companies, it was concluded that the formalization average reached 81.39%, and there was no relationship between the level of formalization and the level of gross sales, because there were many highly formalized companies whose sales were reduced and companies in the opposite scenario.
Keywords: MSMEs; retail trade; processes; administrative formalization; gross sales